Treatment of osteoporosis with eldecalcitol, a new vitamin D analog: a comprehensive review and meta-analysis of randomized clinical trials [Corrigendum] - Xu Z; Fan C; Zhao X; Tao H (Dove Medical Press, 2016)
Zhixing Xu,1 Changchun Fan,2 Xuechun Zhao,3 Hairong Tao11Department of Orthopedic Surgery, The Third People’s Hospital Affiliated to Shanghai Jiaotong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Orthopedic Surgery, Jinan Military General Hospital,3Department of Orthopedic Surgery, The Third Hospital of Jinan City, Jinan, People’s Republic of ChinaThe authors wish to advise that article type was incorrectly titled as a “Review” paper. The article type should be corrected as an “Original Research” paper.Read the original article